2014
DOI: 10.1177/1356766713507514
|View full text |Cite
|
Sign up to set email alerts
|

Segmenting Taiwanese tourists to China by ethnic identity and generation

Abstract: This research intends to segment Taiwanese tourists to China by ethnic identity and generation. Based on Prentice’s ((2004) Tourist familiarity and imagery, Annals of Tourism Research, 31(4), 923–945, (2006) Evocation and experiential seduction: updating choice-sets modeling, Tourism Management, 27, 1153–1170) work that suggests customers who are more emotionally attached to a destination have more positive destination images, this research proposes that Taiwanese holding different identities and belonging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…While this study is not the first to segment tourists based on their motivation to visit a destination, it is novel in that it deals with tourist shoppers and in that it focuses on a geographical area (Turkey and the Middle East) that has been generally ignored or not treated with the importance it deserves in the tourism literature. Furthermore, most studies are dealing with certain segments of tourist shoppers, such as souvenir shoppers (Hu,Yu, 2007;Swanson, Horridge, 2006), rural tourist shoppers (Carmichael, Smith, 2004), traditional market shoppers (Hsieh, Chang, 2006), mall shoppers (Le Hew, Wesley, 2007), shopping village shoppers (Murphy, et al, 2011), luxury shoppers (Park, et al, 2010) or shoppers from a certain country or region (Chen, et al, 2014;Mak, et al, 1999;Mok, Iverson, 2000) and were conducted in the proximity of different shopping venues. Therefore, the researcher can assume that the tourists approached were motivated to shop in those venues and for those particular products and services.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this study is not the first to segment tourists based on their motivation to visit a destination, it is novel in that it deals with tourist shoppers and in that it focuses on a geographical area (Turkey and the Middle East) that has been generally ignored or not treated with the importance it deserves in the tourism literature. Furthermore, most studies are dealing with certain segments of tourist shoppers, such as souvenir shoppers (Hu,Yu, 2007;Swanson, Horridge, 2006), rural tourist shoppers (Carmichael, Smith, 2004), traditional market shoppers (Hsieh, Chang, 2006), mall shoppers (Le Hew, Wesley, 2007), shopping village shoppers (Murphy, et al, 2011), luxury shoppers (Park, et al, 2010) or shoppers from a certain country or region (Chen, et al, 2014;Mak, et al, 1999;Mok, Iverson, 2000) and were conducted in the proximity of different shopping venues. Therefore, the researcher can assume that the tourists approached were motivated to shop in those venues and for those particular products and services.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 99%
“…The main criteria used for segmentation are: nationality (Jonsson, Devonish, 2008;Kozak, 2002), socio-demographics (Chen, et al, 2014;Jonsson, Devonish, 2008;Mak, et al, 1999), psychographics (Weaver, et al, 1994), tourist behaviour (Frochot, Morrison, 2000;Mak, et al, 1999;Yuksel, Yuksel, 2002), benefits (Frochot, Morrison, 2000;Pesonen, et al, 2011) and expenditure (Diaz-Perez, et al, 2005;Mok, Iverson, 2000). Segmentation of tourists by motivation is one of the most effective methods as it could be used to better understand tourists visiting certain destinations or engaging in certain forms of tourism (Park, Yoon, 2009).…”
Section: Segmentation Of the Shopping Tourism Marketmentioning
confidence: 99%
“…For two locations that share the same language and culture, researchers need to identify some deeper factors to quantify the hidden social distance between mainland China and Taiwan (Chen et al, 2017). Therefore, the historical origin and recent complex relationship between mainland China and Taiwan may be significant factors (Chen et al, 2014). Since 2016, cross‐strait relations have become increasingly tense.…”
Section: Discussionmentioning
confidence: 99%
“…The dilemma of this approach is how to select the appropriate variables, as well as how to use the proper statistical techniques. Different variables have been employed as segment bases, such as travel motivations (Alexandris, Kouthouris, Funk, & Giovani, 2009;Assiouras, Skourtis, Koniordos, & Giannopoulos, 2015;Chen, Bao, & Huang, 2014;Oh, Uysal, & Weaver, 1995), satisfaction (Lee, 2015), ethnic identity (Chen, Wang, Lin, & Jiang, 2014), price sensitivity (Petrick, 2005), and self-concept (Todd, 2001). For instance, Assiouras et al (2015) segmented East Asian tourists who visit Greece based on their travel motivations, wherein the authors identified eight motivation factors and three segments as the "Novelty Seekers," the "Want-it-All," and the "Lowly Motivated."…”
Section: Literature Review Segmentation Studies In Tourism Researchmentioning
confidence: 99%